Structure of the metal clusters in rabbit liver metallothionein - Otvos, James D. (1980)
Cadmium-113 nuclear magnetic resonance ((113)Cd NMR) has been used to determine the structures of the multiple cadmium binding sites in the two major isoproteins of rabbit liver metallothionein. The isotopically (113)Cd-labeled metallothionein used in these studies was isolated from the livers of rabbits that had been subjected to repeated injections of (113)CdCl(2). The native protein isolated from these livers contains an appreciable amount of Zn in addition to Cd, ranging from 2-3 mol per mol of protein out of a total metal content of 7 mol per mol of protein. The (113)Cd NMR spectrum of Cd, Zn-containing metallothionein is quite complex, reflecting the fact that the native protein is a heterogeneous mixture of species containing different relative amounts of Zn and Cd. Replacement of the native Zn with (113)Cd in vitro gave a protein whose (113)Cd NMR spectrum was much simpler, containing eight distinct multiplets with chemical shifts ranging from 611-670 ppm. The origin of the multiplet structures has been shown to be (113)Cd-(113)Cd scalar coupling arising from two-bond interactions between (113)Cd ions linked to one another by bridging cysteine thiolate ligands. The size and structures of the metal clusters in the protein were determined by the application of selective homonuclear (113)Cd decoupling techniques. Analysis of these data showed that rabbit liver metallothionein contains two separate metal clusters, one containing four Cd(2+) ions and the other containing three. These two clusters, whose structures are the same in both isoproteins, have been designated “cluster A” and “cluster B,” respectively. Structures for the clusters are proposed that account for the (113)Cd spin coupling data and the participation of all 20 of the cysteine residues in metal ligation, 11 in cluster A and 9 in cluster B. The appearance in the spectrum of eight multiplets rather than the seven that would be expected on the basis of the number of metal binding sites in the protein is an indication of some residual heterogeneity in the (113)Cd-labeled metallothionein sample. The origin of this heterogeneity is suggested to be the presence of a protein species that lacks metal ions at its cluster B binding sites.